Effectiveness of STEM Learning Based on Design Thinking in Improving Critical Thinking Skills in Science Learning: A Meta-Analysis - Zulyusri Zulyusri; Tomi Apra Santosa; Festiyed Festiyed; Yerimadesi Yerimadesi; Yohandri Yohandri; Abdul Razak; Aulia Sofianora (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effectiveness of Design Thinking-based STEM learning in improving students' critical thinking skills in science learning. This research is a type of meta-analysis research. Data sources in the study came from 100 national and international journals published from 2017-2023. Search for data sources through google scholar, Eric, Wiley, Taylor of Francis, Sciencedirect, and ProQuest. Data collection techniques through direct observation through the journal database. The keywords used in the search are STEM model, Design Thinking, Critical thinking skills and Science learning. Data analysis technique is quantitative descriptive analysis with JSAP application. The effect size of each study on the STEM learning model based on design thinking in science learning is 0.84 with large criteria. The results of the study can be concluded that the STEM learning model based on design thinking is effective for improving critical thinking skills in science learning. STEM learning model based on design thinking is very good to be applied in science learning in Indonesia